Feasibility Model of Controlled Atmosphere Storage Implementation for Shallot Farmers in West Java - Herawati, Herawati; Muflikh, Yanti Nuraeni; Rosiana, Nia; Dewi, Triana Gita (Jurnal AGRISEP, 2024)
Smart postharvest technology in the form of Controlled Atmosphere Storage (CAS) is needed to increase the shelf life of shallot.  However, the application of CAS requires high investment costs related to the initial setup such as land, warehouse, CAS, and CAS supporting equipment. Thus, it is necessary to analyze the benefits and costs for farmers' welfare reflected by adding the amount of farming margin and income from other sources considering the time adjustment. This study aims to build a dynamic model for the application of CAS technology in shallot farming and evaluate its costs and benefits for farmers' welfare. The method used is the integration of cost and benefit analysis into a dynamic system model. The results showed that shallot farmers’ income is very sensitive to price changes and increasing storage costs. Hence, adopting CAS technology could mitigate some of these effects by reducing post-harvest losses and allowing farmers to store their production in favorable situations. Moreover, the CAS model showed that in the management level, CAS could be feasible (in terms of NPV, IRR, and Net B/C), if the storage cost is at least IDR 2.000/kg. According to the minimum profit limit for farmers, the maximum storage cost is IDR 1.500/kg, which makes the CAS unfeasible to run. The successful adoption of CAS is contingent upon substantial financial support from both private-sector investors and government entities. Therefore, the CAS technology is more appropriate for adoption by stakeholders in the food industry who require a consistent year-round supply of shallots.